2013
DOI: 10.1155/2013/705027
|View full text |Cite
|
Sign up to set email alerts
|

Endocan in Cancers: A Lesson from a Circulating Dermatan Sulfate Proteoglycan

Abstract: As most proteoglycans exert their biological activities in the pericellular region, circulating Endocan has appeared since its discovery as an atypical dermatan sulfate proteoglycan, with distinctive structural and functional properties. Endocan is naturally expressed by endothelial cells, highly regulated in presence of proinflammatory and proangiogenic molecules, binds to matrix proteins, growth factors, integrin, and cells, and may be then considered as an accurate marker of endothelial activation. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 86 publications
2
109
0
2
Order By: Relevance
“…A newly proposed endothelial marker, endocan, was found to be correlated with vascular inflammatory responses in various conditions, such as sepsis, cancer, and even atherosclerosis [17,18,19,20]. In a recent, comprehensive study, Lee et al [14] demonstrated that endocan elicits proinflammatory responses, such as hyperpermeability, cytoskeleton rearrangement, upregulation of the cellular adhesion molecule expression, leukocyte adhesion and migration via interaction with mitogen-activated protein kinase, signaling pathways, and NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…A newly proposed endothelial marker, endocan, was found to be correlated with vascular inflammatory responses in various conditions, such as sepsis, cancer, and even atherosclerosis [17,18,19,20]. In a recent, comprehensive study, Lee et al [14] demonstrated that endocan elicits proinflammatory responses, such as hyperpermeability, cytoskeleton rearrangement, upregulation of the cellular adhesion molecule expression, leukocyte adhesion and migration via interaction with mitogen-activated protein kinase, signaling pathways, and NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact regulatory mechanism of endocan production is not well established, recent studies suggest that a number of signaling pathways and bioactive mediators are involved. The expression of endocan is upregulated by VEGF-A, VEGF-C, tumor necrosis factor-α, and transforming growth factor-β1 (Lassalle et al 1996;Rennel et al 2007;Maurage et al 2009;Delehedde et al 2013). Because of these relations between endocan and VEGF, we compared the diagnostic efficiencies of VEGF and endocan with carcinoembryonic antigen (the tumor marker that currently provides the best diagnostic accuracy (Shi et al 2008) and CYFRA.…”
Section: Discussionmentioning
confidence: 99%
“…4 It belongs to a set of 6 genes specifically overexpressed during the angiogenic switch. 5 In human tumors, endocan is overexpressed by endothelial cells from various cancers such as non-small lung cancer, hepatocarcinoma, kidney cancer, glioblastoma, and bladder cancer. 5 Multiple studies identified endocan expression as part of molecular signatures defining a poor prognosis in non-small lung cancer, breast cancer, glioblastoma, and hepatocarcinoma.…”
Section: What Is Human Endocan?mentioning
confidence: 99%
“…5 In human tumors, endocan is overexpressed by endothelial cells from various cancers such as non-small lung cancer, hepatocarcinoma, kidney cancer, glioblastoma, and bladder cancer. 5 Multiple studies identified endocan expression as part of molecular signatures defining a poor prognosis in non-small lung cancer, breast cancer, glioblastoma, and hepatocarcinoma. 5 In mice models of tumor xenografts, overexpression of human endocan induces tumor growth of nontumorigenic HEK293 (human embryonic kidney) cells and accelerate tumor growth of the tumorigenic HT-29 cells.…”
Section: What Is Human Endocan?mentioning
confidence: 99%
See 1 more Smart Citation